Dinâmica da vegetação em remanescente de floresta estacional subtropical - Sccot, Marta Silvana Volpato (2012)
The aim of this work was to study vegetation groupings and their dynamics in remnant of Subtropical Seasonal Forest, of nearly 560 ha, located at the Instruction Field of Santa Maria, in Santa Maria municipality, RS. In the study area, 14 blocks of 20x100m were marked, distributed into four bands, distant 500m from each other. Each block was divided into portions of 10mx10m, resulting in 280 portions, in which was evaluated the adult vegetation, represented by individuals with CBH≥30cm. Inside these blocks, 70 portions were raffled for evaluation of understory vegetation (3,14cm≤CBH<30cm), seedling bank (h≥30cm and CBH<3,14cm) and seed rain. In the 70 raffled portions, it was also evaluated the alternation degree, land slope and the light intensity. The occurred changes in the forest shrubby-arboreal component were studied based on the structure, ingress, mortality and increment (for the seedling bank) during the period from 2008 to 2010. In a similar way, the seed rain was monitored from October 2008 to October 2010, when the absolute density and the seasonality of seed production were evaluated. In this study, the results were presented in four chapters: the aim of the first one was to determine the grouping analysis and the occurred changes in the floristic composition and vegetation structure represented by CBH≥30 cm, being verified that the area presents two characterized formations, mainly, by the forest conservation degree, named: - Secondary Forest in Intermediate Stage (SFIS) of succession, represented by bigger exploration in the past due to the easy access to the area; and Secondary Forest in Advanced Stage (SFAS) of succession, occurring in a forest area characterized by a more accentuated slope, what made timber exploitation difficult, being therefore, in a more advanced stage of succession. The second chapter dealt with the occurred changes in the understory vegetation (3,14cm≤CBH<30cm) for the two floristic groups observed in the grouping analysis. In the third chapter, it was presented the natural regeneration dynamics, represented by the seedling bank (h≥30cm e CBH<3,14cm) and the seed rain. Finally, in the fourth chapter, it was carried out a general analysis of the most abundant species dynamics in each class of vegetation, in the two observed groups in the forest. The results indicated some differences in the floristic composition and vegetation dynamics, in each group. In one hand, the SFIS presented the highest value of importance to the heliophilous species and the highest dynamics, mainly, in the individual s mortality. On the other hand, the SFAS presented heliophilous and sciaphilous species as the most important as well as the highest equilibrium in relation to ingress and mortality rates. The seed rain seemed an efficient mechanism of natural regeneration and most of the observed species in the forest s arboreal vegetation presented production seasonality. In general, the remnant of forest represents an important preservation area for the characteristic species from Subtropical Seasonal Forest and its maintenance becomes important to keep the quality of soil in the area besides of playing important environmental services to the region.